Acrylonitrile-Styrene-Acrylate Particles with Different Microstructure for Improving the Toughness of Poly(styrene-co-acrylonitrile) Resin. (11th September 2021) - Zhang, Yuanying; Zhang, Xuechun; Cao, Yongbin; Feng, Jiachun; Yang, Wuli
Abstract : Herein, acrylonitrile-styrene-acrylate copolymer (ASA) particles with different microstructure were synthesized by emulsion polymerization and then used for toughening poly(styrene- co -acrylonitrile) (SAN) resin. The structure of ASA particles was confirmed by FTIR. TEM results demonstrated that the particles with different morphologies of multilobe shape, complete core-shell and dumbbell shape were obtained depending on the cross-linker amount. It was found that the toughening efficiency reached the highest when the ASA particles had complete core-shell structure and the shell composition was close to that of the SAN matrix. It was ascribed to the fact that the complete shell layer and similar shell composition provided sufficient interfacial adhesion and transferred stress to induce larger matrix deformation, so that the notched impact strength increased accordingly. Moreover, the notched impact strength of SAN/ASA blend was improved without significantly sacrificing tensile strength when adding 30 wt% ASA particles with the size of around 400 nm. SEM results of the impact-fractured surfaces revealed that irregular fluctuation and numerous microvoids occurred. It was deduced that the toughening mechanism was attributed to the crazings and cavitation of particles. Therefore, this study paved a way of toughening the resin by adjusting the microstructure of the particles including morphology, composition, and size.